Seroprevalence of human immunodeficiency virus, hepatitis B virus, and hepatitis C virus in patients undergoing nasopharyngeal biopsy - Muhammet Yildiz; Erdem Atalay Cetinkaya; Hulya Eyigor; Omer Tarik Selcuk; Nevreste Didem Sonbay Yilmaz; Nuray Ensari; Nilgun Gur; Ozer Erdem Gur (Medicine Science, 2020)
Objectives:We aimed to determine the seroprevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) in patients undergoing nasopharyngeal biopsy (NPB). Materials and Methods: The medical records of patients who had undergone NPB under local anesthesia between 2009 and 2020 were retrospectively analyzed in our clinic. The hepatitis B surface antigen (HBsAg), HCV antibody (anti-HCV), and HIV antibody (anti-HCV) were recorded in all patients. Age, gender, and pathology result of the patients were also recorded. The patients were divided into two groups (benign and malignant) according to the pathology results. The study included 666 patients with a mean age of 38.5±17.2 years (range, 6-89 years). Serology positivity was detected in 18 patients (2.7%) for HBsAg, in 4 patients (0.6%) for anti-HCV, and in 2 patients (0.3%) for anti-HIV. All serology-positive patients were older than eighteen. The HBV seropositivity rate was significantly higher in males (p=0.003). No statistically significant difference was found between male and female genders for HCV and HIV seropositivity (p>0.05). Reactive lymphoid hyperplasia (70.7%) and chronic inflammation (27.8%) were the most common results in the benign group. Undifferentiated Nasopharyngeal Carcinoma (58.9%) and B-cell non-Hodgkin lymphoma (17.8%) were the most common subtypes in the malignant group. There was no statistically significant difference between benign and malignant groups for HBV, HCV, and HIV seropositivity rates (p>0.05). Preoperative serological testing in patients undergoing NPB is required for increasing awareness of HBV, HCV, and HIV infections among healthcare personnels. Otolaryngologists must have the highest awareness of occupational infections deriving from blood and body fluids. It is necessary to take precaution measures including personal protective equipment during procedures. [Med-Science 2020; 9(4.000): 872-6]